Anti-suit injunction in the context of arbitration agreement - Muhammad Sudin, Mazlin (2022)
Anti-suit injunction is one of an important solution when dealing with parallel proceeding in between litigation and arbitration proceedings and demanded the parties to return to agreed arbitration forum. The parallel proceedings are undesirable for both parties in the contract and may cause conflict to the jurisdiction and dispute of judgement. Although, this injunction may be applied as one of powerful remedies to return to agreed proceeding, the order by the court may cause interference with another foreign court. Thus, anti-suit injunctions may be granted with caution but not carelessly. Courts will consider any exceptional circumstances that make it appropriate for the case to be determined. Therefore, it is important to examine and identify the grounds by the courts in granting and refusing an anti-suit injunction in arbitration civil law proceedings. Globally, legal systems are usually based on either common law or civil law, or in certain situation, a hybrid of the two. As the application of anti-suit injunctions could be applied internationally, the application is governed by UNCITRAL Model Law and the enforcement of anti-suit injunctions, particularly in international arbitration, will be based on the New York Convention, but is it to be noted that there are various restrictions of application and enforcement of anti-suit injunction in civil law legal system especially in Recast Brussels Regulations (amended from the Brussels I Regulation). In arbitration context, the existence and validity of arbitration agreement are crucial to determine that one of the parties had violated the arbitration agreement and pursue the case in the wrong forum, thus, the anti-suit injunction will take the position to prevent the proceedings to be continued. An arbitration agreement to be written in simple and plain terms to eliminate confusion, risk of time and expense, as it may litigated in wrong forum. Moreover, lack of consideration during drafting might result in inconsistency, confusion, and inoperability of the arbitration agreement, which can be unfavorable to the parties at later stage. Again, there are two research objectives; (i) to identify grounds by the court in granting an anti-suit injunction in civil law proceeding in the context of arbitration agreement, (ii) to identify grounds by the court in refusing an anti-suit injunction in civil law proceeding in the context of arbitration agreement. To achieve the objectives of the research, 20 cases had been analysed to obtain the grounds that court considers when granting and refusing an anti-suit injunction in the arbitration context. There are four (4) grounds that court consider when granting anti-suit injunctions in arbitration agreement context which are, the foreign proceeding will contravene the arbitration agreement, the jurisdiction of the court in the correct seat to grant injunction, the validity of the arbitration agreement and the rules of interpretation applicable to the arbitration clause. There are also four (4) grounds that court consider when refusing anti-suit injunction in arbitration agreement context such as non-existence of the arbitration agreement, the injunction will contravene the Brussel regime, offending international mutual trust and respect (comity), and the stage of the foreign proceedings is too far advanced. Therefore, it is essential to understand the underlying principles of approaches as well as circumstances and consideration by the Court when a party is considered for the application of anti-suit injunctions, especially in the context of arbitration agreements as the application of anti-suit injunction is to protect arbitration agreement.